ABSENCE OF SOCIAL PROTECTION TO MIGRANTS IN BRAZIL IN COVEN-19 PANDEMIC TIMES WITH A FOCUS ON THE RIGHT TO ASSISTANCE BENEFIT - Arry Carvalho , Arielle; Vidal Marcílio Pompeu, Gina (Universidade de Brasília, 2021)
It demonstrates the absence of social protection to which migrants in Brazil are subjected, in the context of the Covid-19 pandemic, with a focus on the right to emergency aid. There is an objection to access to the benefit motivated by the requirement for documents that culminates in the worsening of the condition of socioeconomic vulnerability. It is concluded that the Brazilian State is careless in its duty of social protection to migrants who are invisible to the assistance policies of the pandemic.